Perceived Opinion of Farmers and Researchers towards Jasmine Research Priorities - A. Janaki Rani; M. Manoharan; P.P. Murugan (Journal of Agricultural Extension Management, 2025)
Having achieved self-sufficiency on the food front, the focus of Indian agriculture has shifted to other fields of commercialization. One of the areas that have emerged as a viable diversification option is floriculture. In India, flowers have been grown and used for centuries. Flowers are an integral part of our living. Its use, particularly for religious offerings and social functions is on the increase. This has led to the appreciation of the economic importance of flower cultivation, in addition to the realization of its aesthetic value. During the last decade, increased investments have been made in floriculture as a commercial activity. The availability of diverse climatic conditions facilitated the production of a wide range of flowers throughout the year